Komik Webtoon “Yaa Bunayya” Sebagai Penyampaian Pesan Ketagwaan Remaja Muslim - Basori, Alif; Handriyotopo, Handriyotopo (CITRAWIRA : Journal of Advertising and Visual Communication, 2022)
Webtoons frequently visited by teenagers contain various genres of comic stories, but only a few discuss Islam. The Qur'an has many stories, one of which is the story of Luqman's advice to his son. The webtoon approach to this story is suitable to be conveyed to Muslim youth today so that young people who are the next generation of the nation remain in the corridors of goodness. The design of a webtoon comic tells the story of Luqman. This webtoon character takes ideas from lurik and blangkon motifs, so this design is unique compared to other Islamic comics on the webtoon. Communication strategy via Instagram using the AIDA model to target the target audience.